Anthony Minghella : Interviews - Minghella, Anthony (Book collections on Project MUSE., 2013)
Anthony Minghella: Interviews is an illuminating anthology of in-depth conversations with this important contemporary film director and producer. The collection explores Minghella's ideas on every aspect of the cinematic creative process including screenwriting, acting, editing, the use of music in film, and other topics concerning the role of the film director. Minghella (1954-2008) was a highly regarded British playwright (Made in Bangkok), and television writer (Inspector Morse) before turning to film directing with his quirky, highly regarded first film, Tru.